Digital Islamic Education Management: Elementary School Principals' Strategies in Technology-Based Learning and Administration Transformation - Hamdanah, Hamdanah (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2025)
This study comprehensively examined digital transformation leadership in Madrasah Ibtidaiyah, revealing that successful technology integration depends fundamentally on principals' capacity to navigate complex tensions between modernization and Islamic identity preservation. The research identified five core leadership strategies: visionary technology leadership with clear roadmaps, systematic capacity building through multi-modal professional development, integration of Islamic values in digital content, contextualized blended learning models, and strategic parental engagement. These strategies collectively constitute what we term